Crypto sebagai Sarana Investasi Syariah Berkelanjutan - Najwa Lutfah Mu’minin; Rahmah Fitri Emiati; Nabila Raisa; Ajeng Sekar Sucifa (Universitas 45 Surabaya, 2024)
The development of financial technology is growing rapidly along with the development of technological discoveries. Cryptocurrency is one of the objects of financial technology progress. However, often financial and economic developments cannot be swallowed whole by Muslims. This is because there are laws that regulate economics in Islam. One of the laws that must be discussed is related to Cryptocurrency and Islamic law regarding the value of the new currency. Cryptocurrency is considered to have a fluctuating or uncertain value so that there may be economic practices that are contrary to the benefit of the people. One of the economic practices that this Cryptocurrency can implement is sustainable investment. For this reason, researchers are interested in knowing the relevance and legal status or legitimacy of Cryptocurrency as a sustainable investment through Islamic economic principles. Researchers used descriptive qualitative research methods based on previous research. Based on the results of the research that has been carried out, it can be concluded that crypto assets, both conventional and sharia, cannot yet become sustainable investment assets. Because judging from the data that has been presented, it shows that crypto investments have high fluctuations and volatility. This causes the high risk of crypto assets in investment even though there is the possibility of high profits too.